(3CQHYhf MOjkKG efJbGI ef Sff GdTGaYis - (3CHh MGeO eMeO Hf YHO GdQMef GdeWQi GdCfUGQjs; (3CHh YHO Gddg eMeO Hf EOQjS Hf GdYHGS Hf YKeGf Hf TGaY (B( (3GdEeGe GdTGaYj (B)(3,J (B204 (3g` s ((3eMeO Hf eMeO Hf CHj TQja GdTGaYi s)
(3ChdgG (B:s
(3gPg GQHYhf MOjKkG ef eSfO GdGeGe GdGYXe CHj YHO Gddg eMeO Hf GOQjS GdTGaYi QVi Gddg Yfg MOKfG HgG ef daXI hfMf fSeY HeSLO QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3Yf GHf YeQ Gf QLdkG SCd QShd Gddg Udi Gddg Ydjg hSde Yf UdGg Gddjd abGd QShd Gddg Udi Gddg Ydjg hSde UdGg Gddjd eKfi eKfi aEPG CMOce GdUHM Udi QcYJg BNQ GdGQHYjf GdefJbGg ef eSfO GdGeGe GdTGaYi QVi Gddg Yfg hGQVGg hfaYfG HHQcJg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydjg SeGY ddcGJH hGNjg hLeGYg Ydi eMeO Hf YHO GdQMef GdeWQi HGdeSLO GdfHhi GdTQja hYdjgG NWg hHUMI GdSeGYs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs